Organizational Factors Driving the Realization of Digital Health Transformation Benefits from Health Service Managers: A Qualitative Study - Brommeyer M; Whittaker M; Liang Z (Dove Medical Press, 2024)
Mark Brommeyer,1,2 Maxine Whittaker,1 Zhanming Liang1 1James Cook University, Townsville, QLD, Australia; 2Flinders University, Adelaide, SA, AustraliaCorrespondence: Mark Brommeyer, College of Business, Government and Law, Flinders University, GPO Box 2100, Adelaide, SA, 5001, Australia, Email mark.brommeyer@flinders.edu.auIntroduction: Healthcare is experiencing a global period of profound transformation, and digital health shows the promise of dispensing innovative and contemporary service models. However, changes are required to improve the capabilities of health managers in driving successful digital transformation.Objective: This paper aims to explore the organizational barriers that health service managers have encountered when realizing the benefits of a digitally transforming environment. This is part of a larger research study exploring digital competencies for health service managers, with the findings from focus group discussions providing a baseline from which to address the organizational improvements and changes in system capabilities required to assist in realizing the benefits of digital health transformation.Methods: The study is qualitative in nature. It employs focus group discussions to gain an in-depth understanding of the experiences and views of health service managers and identify the benefits and barriers that managers have experienced in introducing digital health in their workplace.Results: Barriers encountered in realizing digital health benefits in the workplace were evidenced across five major themes: (1) change resistance and usage, (2) trust and uniformity, (3) resourcing and procurement, (4) digital literacy, and (5) siloed systems.Discussion: Findings from this study demonstrate that in driving the realization of digital health transformation benefits, health service managers need organizational and system-wide efforts to support managing in the digital health context. The key identified barriers experienced by health service managers include facing human and technical challenges with system adoption and the governance of data-driven decision-making in the digital context.Conclusion: The importance of digital transformation in healthcare is evident and will increasingly become a necessity for organizational survival and success. This study adds important insights into the organizational barriers that health service managers have encountered when realizing the benefits resulting from digital transformation. Addressing these barriers requires macro-, meso- and micro-level system investments. These benefits are enhanced by enabling factors critical for digital health adoption that have been described in key categories involving health system related: (1) policy and system, (2) organizational structure and processes, and human resource management, and (3) people factors. The importance of ensuring the organizational factors driving the realization of benefits in a digitally transforming environment is also addressed and capitalized upon for health service managers.Keywords: healthcare management, health service manager, digital transformation, digital health benefits, workforce development, digital health barriers